(untitled) (diségno, 2023)
If drawing has always been a tool for expressing the ideational design process, with a strenuous search for synthesis aimed at accelerating the necessary times facilitated by digital introduction, the integrated elaboration capacity of the idea has increasingly been lost. This loss has given rise to partially sterile hypotheses devoid of that world of forms and the search for form, which constitute true architectural and spatial projects. Aldo Rossi’s drawings come to mind, where a coffee maker could become, as we would say today, an essential object in the domestic ritual, a house, but also a tower, a viewpoint, or even part of what he himself called ‘domestic theater’, where pure forms could combine to create, with dimensions not coinciding with reality, simple objects of common use that could become significant elements of interior spaces. We have thus reduced ourselves to no longer knowing how to compose but to seek sophisticated elaborations of volumes that fall into a love for complication rather than a simplification that contemporary reality requires. But if the digital world can ‘bend’ to ideative will, why can’t we integrate it instead of replacing it with what is effectively the project, understood as a process of investigation?